Why Current EU Proposals for Corona-Related Financial Aid Cannot Replace Coronabonds - Sebastian Dullien; Thomas Theobald; Silke Tober; Andrew Watt (Intereconomics)
Abstract With public debt-to-GDP levels now set to surpass post-war records and Italy’s ratio approaching levels reached in Greece on the eve of the country’s debt restructuring in early 2012, fears of a return of the sovereign debt crisis have emerged.